Jay Chou's Zhongguo Feng: Songs and identity / Su Zekai - Su , Zekai (2018)
This study focused on analyzing Zhongguo Feng (China wind，中国风) songs and identity of Jay Chou’s representative work from 2000-2016. Past scholars examined into Zhongguo Feng with labels such as “chinked-out” and “China wind”, however, there is a lack of detailed musical analysis in their work. Therefore, this research attempts to fill in the gap in the study of this area. The objectives of this study are to investigate in what way Jay Chou employed Zhongguo Feng characteristics in his songs, and to analyze music elements representing Zhongguo Feng and its identity. This study is based on a qualitative research theoretical framework and methods include literature review, transcription, score analysis, lyrics analysis, listening analysis, video analysis and virtual fieldwork. The selected songs Chrysanthemums Terrace (菊花台) and Faraway (千里之外) were analysed. The outcome includes a discussion of musical hybridity and the revival of Chinese tradition in C-pop since the shidaiqu (时代曲) in the 1940s.